Familial thyroid ectopy and hemiagenesis. - Rosenberg, T (1980)
Two siblings had sublingual thyroid glands and hypothyroidism. A third sibling had a left lobe agenesis of the thyroid, but normal function of the gland. This is the second such family to be described.